2015
DOI: 10.2217/pgs.15.84
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Slco1B3 and Nr1I2 as Genetic Determinants of Hematotoxicity of Carboplatin and Paclitaxel Combination

Abstract: Our results revealed the importance of SLCO1B3 and NR1I2 in the sensitivity to carboplatin/paclitaxel thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These evidences supported the notion of explaining drug action by the biological functions of drug-related genes [ 39 ]. Therefore, other carboplatin-related genes involved in hematopoietic cell lineage may provide new research routes with regard to the underlying toxicological mechanisms of carboplatin, such as finding polymorphisms associated with hematotoxicity [ 40 ] and differential gene expression involved in hematopoietic lineage [ 41 ]. Experimental validation of these genes will be required to further elucidate the roles they play in the hematologic context.…”
Section: Discussionmentioning
confidence: 99%
“…These evidences supported the notion of explaining drug action by the biological functions of drug-related genes [ 39 ]. Therefore, other carboplatin-related genes involved in hematopoietic cell lineage may provide new research routes with regard to the underlying toxicological mechanisms of carboplatin, such as finding polymorphisms associated with hematotoxicity [ 40 ] and differential gene expression involved in hematopoietic lineage [ 41 ]. Experimental validation of these genes will be required to further elucidate the roles they play in the hematologic context.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of polymorphisms (SNPs) in SLCO1B3 revealed that a number of variants were associated with anti-cancer drug and immunosuppressant drug response or toxicity (see https://www.pharmgkb.org/gene/PA35844/variantAnnotation). For example, patients who are carriers of the T allele of rs4149117 (OATP1B3-Ser112Ala, c.334T>G), were 19% less sensitive to thrombocytopenia from carboplatin/paclitaxel treatment, than the homozygotes for the G allele 65 . SLCO1B3 699GG (rs7311358, OATP1B3-Met233Ile, c.699G>A) and 344TT (rs4149117) genotypes are also associated with non-response to imatinib in patients with chronic myeloid leukemia 66 .…”
Section: Polymorphisms In Other Drug Transporters With Less Evidencementioning
confidence: 99%
“…The effect of SLCO1B3 variation on chemotherapy‐induced toxicities is poorly understood. A SLCO1B3 variant rs4149117 (c.334T>C, p.Ser112Pro), which is in a complete LD with rs7311358 in our data and European population, 31 has been found to reduce, increase, or not affect the risk for toxicities 7,32,33 . Similarly, the mechanism explaining our finding of a reduced risk of severe adverse effects associated with the rs7311358 remains elusive.…”
Section: Discussionmentioning
confidence: 51%